Pengembangan Aplikasi Pembelajaran Multiplatform dengan Desain Mobile dan Desktop Untuk Mendukung Pendidikan Moderen - Taufik Afandi; Khasan Nuzaki; Rahmat Kamal (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
Learning applications are very important in facilitating access to education, supporting independent learning, and increasing the effectiveness of the learning process with interactive features. This article aims to discuss the development of multiplatform learning applications with designs that support mobile and desktop devices as an effort to increase effectiveness and flexibility in modern education. The research approach involves analyzing user needs, designing user-centered design (UCD)-based interfaces, and testing application functionality on various devices. The research method used in this article is research and development. The results of the study indicate that multiplatform applications can increase user engagement and provide wider access to digital learning. This article also reviews the design of mobile and desktop applications, concepts, designs and prototypes, and implementation in relevant learning